Zinc transport and the inhibition of the L-type calcium channel are two separable functions of ZnT-. Issue 3 (16th January 2017) - Shusterman, Eden; Beharier, Ofer; Levy, Shiri; Zarivach, Raz; Etzion, Yoram; Campbell, Craig R.; Lee, Il-Ha; Dinudom, Anuwat; Cook, David I.; Peretz, Asher; Katz, Amos; Gitler, Daniel; et al.
Abstract : ZnT-1 performs two independent and separable functions related to zinc homeostasis: Active zinc transport and L-type calcium channel (LTCC) inhibition. Abstract : Traditionally, proteins are considered to perform a single role, be it as an enzyme, a channel, a transporter or as a structural scaffold. However, recent studies have described moonlighting proteins that perform distinct and independent functions; for example, TRPM7 is both an ion channel and a kinase. ZnT-1 is a member of the Carrier Diffusion Facilitator family that is expressed throughout the phylogenetic tree from bacteria to humans. Since its cloning in 1995, ZnT-1 is considered a major extruder of Zn 2+ based on its capability to protect cells against zinc toxicity. Recently, we reported that ZnT-1 inhibits the L-type calcium channel (LTCC), a major Zn 2+ and Ca 2+ entry pathway. Here we show that ZnT-1 is a dual-function protein by demonstrating that its abilities to exchange Zn 2+ /H + and to inhibit the LTCC are independent of each other and are mediated by different parts of the protein. Specifically, mutations in the membrane-spanning helices that render ZnT-1 unable to transport zinc do not prevent it from inhibiting the LTCC. Moreover, a fragment consisting of the intracellular ZnT-1 C-terminal, which lacks all ion-transfer segments, inhibits the LTCC as efficiently as wild-type ZnT-1. Our data therefore indicates that ZnT-1 performs two structurally independent functions related to zinc homeostasis.